The Cambridge encyclopedia of the English language - Crystal, David, (Cambridge University Press, 2019)
Now in its third edition, The Cambridge Encyclopedia of the English Language provides the most comprehensive coverage of the history, structure and worldwide use of English. Fully updated and expanded, with a fresh redesigned layout, and over sixty audio resources to bring language extracts to life, it covers all aspects of the English language including the history of English, with new pages on Shakespeare's vocabulary and pronunciation, updated statistics on global English use that now cover all countries and the future of English in a post-Brexit Europe, regional and social variations, with fresh insights into the growing cultural identities of 'new Englishes', English in everyday use with new sections on gender identities, forensic studies, and 'big data' in corpus linguistics, digital developments, including the emergence of new online varieties in social media platforms such as Facebook, Twitter and WhatsApp. Packed with brand new colour illustrations, photographs, maps, tables and graphs this new edition is an essential tool for a new generation of twenty-first-century English language enthusiasts.